Understanding Millennial relationships and consumption of no and low alcohol beer brands - Elizabeth Steinhobel; Mornay Roberts-Lombard; Isolde Lubbe (South African Journal of Business Management)
Purpose: The purpose of the study is to determine the influence of brand image on brand relationships (brand satisfaction, brand trust and brand attachment), and the impact of these relationships on the current and future consumption of millennial consumers’ no and low alcohol (NoLo) beer brands. It also explored the moderating role of traditional word of mouth (WOM) and electronic word of mouth (eWOM) on the relationship between current and future consumption.